Penerapan Metoda Geolistrik Tahanan Jenis untuk Menentukan Tanah Longsor (Studi Kasus: Longsor di Desa Nasol Kabupaten Ciamis) - Nor, Muhammad (Jurnal Pilar Sains, 2005)
Geoelectric survey at countryside of Nasol District of Penambangan Province of West Java has beenusing Wenner – schlumberger resistivity configuration with one lines. The path length measurement ofgeoelectrical is 230 m eith electrode space distance 10 m. The result of survey is indicated landslide ofNasol area with slope inclination angle 450, Which is main scarp about 2-4 meter with rotationaldirection. The landslide of with bsoutheast – northwest direction. Pursuant to 2D geoelectric section incountryside of Nasol can be interpreted there is trihedron slip with type of between 11.6 – 379ohmmeter, seen that in of survey area have caused process ground movement at slip area with deepnessvariation between 30 – 40 m.